RECONSTRUCTION OF MARRIAGE IN THE PERSPECTIVE OF ISLAMIC LAW: RENEWAL EFFORTS TO ACHIEVE SUSTAINABLE AND HAPPY HOUSEHOLDS - Muhammadong Muhammadong (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2026)
Marriage in the perspective of Islamic law is based on a strong foundation as a sacred institution, aimed at achieving a harmonious, loving, and compassionate family life. However, with the dynamics of society and changes over time, the challenges in maintaining a lasting and happy marriage have become more complex. This study aims to explore the concept of marriage reconstruction in the perspective of Islamic law, focusing on renewal efforts that can ensure the sustainability and happiness of households. The research method used is a literature review with a qualitative approach, examining classical and contemporary texts on marriage in Islamic law, as well as interviews with religious and community figures. The findings reveal that marriage reconstruction in Islam not only emphasizes the re-understanding of the rights and obligations of spouses but also highlights the importance of spiritual approaches, effective communication, and wise conflict resolution. The conclusion of this study is that renewal in marriage practices is essential to address modern issues faced by couples, such as inequality, role differences, and a lack of understanding about marriage rights. With proper reconstruction, marriage can serve as a stronger foundation for achieving a sustainable and happy family life.